Identification of Some Oat Cultivars (Avena sativa L.) By Uusing Morphological Characters of T the Spikes - A. Bashi; A. Jabar (College of Education for Pure Sciences, 2019)
This study was conducted in the wired house and the laboratories of the Department of Biology, College of Education, Mosul University, in the period extended from 1/4/2009 until 1/11/2009 to study many morphological characters of all the five imported cultivates of oat plants (Possum 6, Kangaroo 4, Oat Tall, Mittika 5, Oat Short). The results of this study were statistically analyzed according to Complete Randomized Design. The statistical results were considered significant at P≤0.05. The results showed significant differences in many of the morphological characters of all the five cultivars including length and shape of rachis, peduncle length, pedicle length, Arrangement of spike, Glumes length, Hairs on the lemma, Awn length, Ligules height and shape. In conclusion; it is possible to identify and classify these five Oats cultivars by studying the morphological characters of its spikes.